Disclosure of Stakeholder Engagement, Proportion of Women on The Board of Directors, and Profitability (E-Jurnal Akuntansi, 2026)
The tourism sector has a high dependence on social acceptance and stakeholder engagement, so sustainability practices are a strategic issue for companies. This study aims to analyze the influence of the proportion of women on the board of directors and the profitability of companies on the disclosure of stakeholder involvement in tourism sector companies in Indonesia. The study uses data on tourism companies listed on the Indonesia Stock Exchange for the period 2023–2024, with the measurement of stakeholder involvement referring to the GRI 2-29 indicator. The analysis was carried out through multiple linear regression with profitability as the control variable. The results showed that the proportion of women on the board of directors and the profitability of the company did not have a significant effect on the disclosure of stakeholder engagement. These findings indicate that women's representation on boards is still symbolic and has not been accompanied by a substantive role in driving sustainability practices. This study emphasizes the relevance of Feminism Theory in exposing the structural and cultural limitations of corporate governance in Indonesia's tourism sector.
Keywords: Proportion of Women; Board of Directors; Profitability; Theory of Feminism